พาสต้าเสริมเส้นใยจากแป้งถั่วแดงหลวง - ทิพย์รักษา จิรนาถ; นุดวงแก้ว สุภักษร (Journal of Food Technology, Siam University, 2015)
ศึกษาการผลิตพาสต้าจากแป้งถั่วแดงหลวงทดแทนแป้งเซโมลินาบางส่วน โดยแปรปริมาณแป้งถั่วแดงหลวงที่ระดับร้อยละ 5, 10, 15, 20, 25, และ 30 (โดยน้ำหนักแป้ง) เมื่อวิเคราะห์ค่าสีของผลิตภัณฑ์พาสต้าจากแป้งถั่วแดงหลวง พบว่าค่าความสว่าง (L*) และค่าสีเหลือง (b*) ลดลง ในขณะที่ค่าสีแดง (a*) เพิ่มขึ้นเมื่อปริมาณแป้งถั่วแดงหลวงที่ใช้ทดแทนเพิ่มขึ้น ร้อยละของน้ำหนักที่หายไปในการต้ม (Cooking loss) เพิ่มขึ้น (4.20-5.01%) โดยสูตรที่ทดแทนแป้งถั่วแดงหลวงปริมาณร้อยละ 10 มีค่า Cooking loss ต่้าสุด ค่าการพองตัวจะลดลงตามปริมาณแป้งถั่วแดงหลวงที่ใช้ทดแทนมากขึ้น จากการประเมินคุณภาพทางประสาทสัมผัส พบว่าผลิตภัณฑ์ที่ทดแทนด้วยแป้งถั่วแดงหลวงที่ระดับร้อยละ 20 ผู้บริโภคให้การยอมรับมากที่สุด มีค่าความแข็งแรงมากกว่าและระยะขาดของเส้นน้อยกว่าสูตรมาตรฐาน โดยให้ปริมาณโปรตีน เส้นใย และเถ้าสูงกว่าสูตรมาตรฐาน Pasta Supplemented Dietary Fiber from Red Kidney Bean Flour Study on production of pasta from semolina flour partially substituted with red kidney bean flour. The red kidney bean flour was varied at 5, 10, 15, 20, 25 and 30% (by flour weight). The measurement of color of pasta found that the L* and b* value were decreased while the a* value was increased when increasing red kidney bean flour. The cooking loss of all products was between 4.20-5.01% and the 10% red kidney bean flour pasta had the lowest cooking loss. The water swelling was decreased with increasing red kidney bean flour. The sensory evaluation of pasta, i.e. appearance, color, stickiness, taste and all acceptability was tested. The appearances and color among the samples had different significantly (p0.05). The 20% red kidney bean flour pasta had the most acceptances. The 20% red kidney bean flour pasta had tensile strength more than standard formula while the distance was lower. The chemical compositions of standard and optimal formula (20% red kidney bean flour) were analyzed. The content of protein, fiber and ash of the optimal formula were higher than standard formula.